Dispentation of Underage Marriage in Islamic Societies in Parepare City (Case Study at parepare Class 1B Religious Court 2022) - Muhammad Khairul; iin Mutmainnah; Muh. Jafar; Mohamad Jusuf Husain Isa (Jurnal Marital: Kajian Hukum Keluarga Islam, 2022)
According to fuqoha and jurists, they agreed to stipulate that people who are mature enough will be held accountable for each and have the freedom to determine their lives. By referring to the applicable law, the prospective bride and groom who are under 19 years of age are considered not old enough to marry and are not yet competent in the eyes of the law. There are three factors that cause marriage dispensation, among others, namely the factor of getting pregnant before marriage, economic factors, and educational factors. And what is the basis for the judge's consideration in making a marriage dispensation decision is the law but requires ijtihad based on the benefit of mursalah.